A first order Tsallis theory - Ferri, Gustavo L. (2017)
We investigate first-order approximations to both (i) Tsallis’ entropy Sq and (ii) the Sq-MaxEnt solution (called q-exponential functions eq).We use an approximation/expansion for q very close to unity. It is shown that the functions arising from the procedure (ii) are theMaxEnt solutions to the entropy emerging from (i). Our present treatment is motivated by the fact it is FREE of the poles that, for classic quadratic Hamiltonians, appear in Tsallis’ approach, as demonstrated in [A. Plastimo, M.C. Rocca, Europhys. Lett. 104, 60003 (2013)]. Additionally, we show that our treatment is compatible with extant date on the ozone layer.